Science projects about weather - Gardner, Robert, 1929-; Delisle, Stephen F.; Webster, David, 1930- (Berkeley Heights, N.J. : Enslow, 1994)
Contains a variety of projects related to all aspects of the weather.
Includes bibliographical references (p. 121) and index.
Book Report.
School Library Journal.
Wilson's Junior High School.
Young Adult
Keywords: Science projects -- Juvenile literature; Science -- Exhibitions -- Juvenile literature; Weather -- Experiments -- Juvenile literature; Experiments; Science projects; Weather -- Experiments; Science projects; Science -- Experiments; Weather -- Experiments